Experimental Impact of Drought on Germination of Upland Rice Using PEG 6000 - Sakka Samudin (Research Advances and Challenges in Agricultural Sciences Vol. 8, 2024)
This study aims to detect early drought tolerance of upland rice cultivars during germination. Sealing plants with better drought tolerance is especially important in dry environments. However, drought simulation that is controlled and uniformly repeated in the field cannot be easily achieved. Climate change in the form of drought will reduce agricultural production, so it is necessary to develop superior drought-tolerant varieties. This experimental study was arranged with a factorial pattern of two factors using a Completely Randomized Design from September to December 2021 at the Seed Science and Technology Laboratory, Faculty of Agriculture, Tadulako University, Palu, Center Sulawesi, Indonesia. Twelve cultivars comprised the first factor, while two superior drought-resistant variants served as comparators. The second factor is osmotic stress, namely P0 = control, P1 = -1 bar, P2 = -2 bar, and P3 = -3 bar, so there are 56 treatment combinations repeated four times, so there are 224 experimental units. The observed variables were maximum growth potential, germination rate, radicle length, plumule length, radicle dry weight, plumule dry weight, sprout dry weight, water volume, and germination rate. Delay in seed germination caused by PEG administration up to -3 bar has caused metabolic disturbances such as slower hydrolysis of storage compounds in the endosperm or cotyledons and slower transport of the hydrolyzed material to the axis of the developing embryo under drought conditions.